Collagen sheet dressings for cutaneous lesions of toxic epidermal necrolysis - S. Bhattacharya; H. N. Tripathi; V. Gupta; Bharti Nigam; A. Khanna (Indian Journal of Plastic Surgery)
Toxic epidermal necrolysis (TEN) is associated with a significant mortality of 30–50% and long-term sequelae. Treatment includes early admission to a burn unit, where management with precise fluid, electrolyte, protein, and energy supplementation, moderate mechanical ventilation, and expert wound care can be provided. Specific treatment with immunosuppressive drugs or immunoglobulins did not show an improved outcome in most studies and remains controversial. We have treated the cutaneous lesions of seven patients of TEN with collagen sheet dressings and have found a significant reduction in morbidity. The sheets are a one-time dressing, easy to apply and they reduce fluid loss, prevent infection, reduce pain, avoid repeated dressings and gradually peal off as the underlying lesions heal.